Supply Chain Management in the Contemporary Fashion Industry - Mongkolsin, Thanotai (วารสารนักบริหาร, 2015)
The fashion industry is an industry that has to cope with uncertainties. Everything can vary from the current fashion trends. Contemporary fashion industry is an industry that is focused on designing and manufacturing fashion clothing and products that meet the consumer needs of which following fashion trends is the main goal. This article discusses how to apply the supply chain management implementation to the contemporary fashion industry by using three strategies, including Just in Time Strategy, Agile Supply Chain Strategy, and Quick Response Systems Strategy. The author raised an example of Zara brand as a hugely successful brand which originally runs the business with fast fashion strategy by using the information technology systems and the supply chain management. In addition, the article also discusses the obstacles, possible solutions and the future trends of the supply chain management in the contemporary fashion industry in Thailand. การจัดการห่วงโซ่อุปทานในอุตสาหกรรมแฟชั่นร่วมสมัย อุตสาหกรรมแฟชั่นเป็นอุตสาหกรรมที่ตั้งอยู่บนพื้นฐานของความไม่แน่นอน ทุกอย่างล้วนเปลี่ยนผันไปตามกระแสแฟชั่นที่หมุนตามแนวโน้มทางแฟชั่น อุตสาหกรรมแฟชั่นร่วมสมัยเป็นอุตสาหกรรมที่มุ่งเน้นการออกแบบและผลิตเสื้อผ้าและสินค้าแฟชั่นที่ตอบสนองความต้องการของผู้บริโภคที่ตามแนวโน้มทางแฟชั่นเป็นเป้าหมายหลัก บทความนี้จะกล่าวถึงการนำการจัดการห่วงโซ่อุปทานมาประยุกต์ใช้ในอุตสาหกรรมแฟชั่นร่วมสมัย โดยนำเสนอกลยุทธ์ 3 แบบ อันได้แก่ กลยุทธ์ทันเวลาพอดี กลยุทธ์ห่วงโซ่อุปทานที่มีความคล่องตัว และกลยุทธ์ความรวดเร็วในการส่งมอบสินค้า อีกทั้งยกตัวอย่างของตราสินค้า Zara ซึ่งเป็นตราสินค้าผู้เริ่มต้นแนวความคิดการนำกลยุทธ์แฟชั่นรวดเร็ว โดยอาศัยระบบเทคโนโลยีสารสนเทศและการจัดการห่วงโซ่อุปทานมาใช้ดำเนินธุรกิจ จนประสบความสำเร็จอย่างมหาศาล นอกจากนี้ ยังกล่าวถึงอุปสรรคและแนวทางแก้ปัญหา รวมถึงแนวโน้มในอนาคตของการจัดการห่วงโซ่อุปทานกับอุตสาหกรรมแฟชั่นของไทย